(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
In the face of public society, the judiciary may be forced to change the decisions already signed, since sometimes they are no longer effective. However, by moving towards the search for effectiveness of decisions, changing them, notably as binding effect points, linked to the institute of legal certainty, as it affects the evaluations of individuals with expected result. Given this, the modulation of the effects of decisions aims to preserve legal certainty, and precisely for this reason, the effect of modulation will be prospective, allowing both security and use. This, which, by contrast, an application retroactively, directly affects the freedom and property of citizens who rely on the judiciary, causing a situation of total insecurity.